Paideia Kristiani sebagai Ontologi Pendidikan Agama Kristen: Formasi Spiritualitas dan Etika Generasi Muda dalam Terang Alkitab - Rosianna Purba (EPIGRAPHE (Jurnal Teologi dan Pelayanan Kristiani), 2023)
Christian paideia, as the ontological foundation of Bible-based Christian education, affirms that education is not merely a vehicle for transmitting knowledge but a formative process that shapes the very essence of human existence before God. This study examines Christian paideia as a paradigm that integrates faith, knowledge, and ethical praxis to form the younger generation. Employing a qualitative method grounded in a literature study and informed by hermeneutical and pedagogical approaches, this research engages Scripture as a normative source in dialogue with contemporary literature on the theology of education. The findings reveal that Christian paideia operates across four intertwined dimensions: first, as an ontology and existential formation that shapes the whole person as imago Dei; second, as a space integrating faith, spirituality, and ethics, manifested in honesty, justice, and love; third, as a contextual paradigm responding to moral crises in the digital and global era while serving as a moral-spiritual filter; and fourth, as the basis for communal, theological, and pedagogical implications for Christian education. Christian paideia thus emerges as an educational paradigm that transcends cognitive acquisition, forming faithful and ethical persons who contribute meaningfully to communal life. Abstrak Paideia Kristiani sebagai fondasi ontologis pendidikan Agama Kristen berbasis Alkitab menegaskan bahwa pendidikan bukan sekadar sarana transfer pengetahuan, melainkan proses formasi eksistensial yang menyentuh inti keberadaan manusia di hadapan Allah. Artikel ini menelaah paideia Kristiani sebagai paradigma yang mengintegrasikan iman, pengetahuan, dan praktik etis dalam pembentukan generasi muda. Dengan menggunakan metode kualitatif berbasis studi literatur dan pendekatan hermeneutik-pedagogis, kajian ini menempatkan Alkitab sebagai sumber normatif dalam dialog dengan literatur teologi pendidikan kontemporer. Hasilnya menunjukkan bahwa paideia Kristiani beroperasi pada empat dimensi yang saling berkelindan: pertama, sebagai ontologi dan formasi eksistensial yang membentuk manusia seutuhnya sebagai imago Dei; kedua, sebagai ruang integrasi iman, spiritualitas, dan etika yang termanifestasi dalam kejujuran, keadilan, dan kasih; ketiga, sebagai paradigma kontekstual yang menjawab krisis moral di era digital dan globalisasi, sekaligus berfungsi sebagai filter moral dan spiritual; dan keempat, sebagai dasar implikasi komunitarian, teologis, serta pedagogis bagi pendidikan Kristiani. Dengan demikian, paideia Kristiani tampil sebagai paradigma pendidikan yang melampaui dimensi kognisi semata dan membentuk pribadi yang beriman, beretika, serta berkontribusi bagi kehidupan bersama.